Seaweed Extract-Stimulated Priming in Arabidopsis thaliana and Solanum lycopersicum - Md Tohidul Islam; Tony Arioli; David M. Cahill (Plants, 2021)
Plant priming is an induced physiological state where plants are protected from biotic and abiotic stresses. Whether seaweed extracts promote priming is largely unknown as is the mechanism by which priming may occur. In this study, we examined the effect of a seaweed extract (SWE) on two distinct stages of plant priming (priming phase and post-challenge primed state) by characterising (i) plant gene expression responses using qRT-PCR and (ii) signal transduction responses by evaluating reactive oxygen species (ROS) production. The SWE is made from the brown algae Ascophyllum nodosum and Durvillaea potatorum. The priming phase was examined using both Arabidopsis thaliana and Solanum lycopersicum. At this stage, the SWE up-regulated key priming-related genes, such as those related to systemic acquired resistance (SAR) and activated the production of ROS. These responses were found to be temporal (lasting 3 days). The post-challenge primed state was examined using A. thaliana challenged with a root pathogen. Similarly, defence response-related genes, such as PR1 and NPR1, were up-regulated and ROS production was activated (lasting 5 days). This study found that SWE induces plant priming-like responses by (i) up-regulating genes associated with plant defence responses and (ii) increasing production of ROS associated with signalling responses.